Exploring tourism-generated social media communication, brand equity, satisfaction, and loyalty: A PLS-SEM-based multi-sequential approach - Abbasi, A.Z. (2022)
Although social media-based brand equity has become a vital area of interest for brand managers, insights into its destination-based dynamics and applications remain scarce, specifically in the destination brand context. To address this gap, we develop and test a theoretical model to investigate the role of destination marketing organization-generated and tourist-generated social media communication to determine the brand awareness and brand image of the Gilgit-Baltistan region, which in turn influence customer-based brand equity (CBBE) (i.e. perceived quality), satisfaction, and loyalty. Data come from well-known tourist sites in Gilgit-Baltistan. Using the multi-sequential approach in WarpPLS 7.0, findings shows that the social media communication dimensions show differential impacts on brand awareness as a metric of CBBE. Second, destination awareness demonstrates a differential impact on perceived destination image dimensions. Third, the destination image dimensions exert different effects on the perceived quality of the destination. Fourth, perceived quality positively influences satisfaction, which in turn enhances loyalty. We offer important implications that emerged from the analyzes and also suggest directions for future research. Â© The Author(s) 2022.